Inovasi Pembelajaran Bahasa Arab di Pesantren: Antara Mempertahankan Tradisi dan Tuntutan Modernisasi - Moh. Naqib (Journal of Innovative and Creativity, 2025)
Purpose. This study aims to analyze the dynamics of Arabic language education innovation in Indonesian Islamic boarding schools (pesantren) through a comprehensive literature review. Pesantren, as the oldest Islamic educational institution in Indonesia, faces the challenge of maintaining the tradition of Arabic learning while adapting to modernization demands. This research identifies various forms of innovation, analyzes driving and inhibiting factors, evaluates effectiveness, and develops a conceptual framework that balances tradition and modernization in Arabic language education. Materials and methods. The research employs a qualitative literature review approach by analyzing 45 scientific articles, books, and research reports published between 2015-2024. Analysis was conducted thematically on aspects of teaching methods, curriculum, learning media, and educator competencies. Data sources were obtained from Google Scholar, Portal Garuda, DOAJ, ResearchGate, and institutional repositories through systematic search and screening processes. Thematic analysis was employed through open coding, axial coding, and selective coding stages to identify patterns and develop conceptual frameworks. Results. The study reveals four major themes of Arabic language education innovation in pesantren: (1) integration of classical methods (sorogan, bandongan) with modern communicative methods through eclectic approaches, (2) development of competency-based curriculum accommodating kitab kuning, fusha Arabic, and communicative skills with flexible leveling systems, (3) utilization of digital technology including e-learning, mobile applications, and social media platforms for extended learning environments, and (4) strengthening of ustadz pedagogical competencies through professional training, academic qualification enhancement, and communities of practice. Supporting factors include visionary kyai leadership, adequate resources, open organizational culture, and networking with external institutions, while inhibiting factors include traditionalist resistance, resource limitations, and challenges in harmonizing innovation with pesantren core values. Conclusions. Successful innovations are those that balance the preservation of Islamic scholarly traditions with practical needs of contemporary Arabic language mastery. The conceptual framework developed offers guidance for pesantren to implement innovation based on five principles: continuity and change, contextualization, holistic integration, participation, and continuous evaluation. The ultimate goal is to produce santri with trilateral competencies: classical (understanding kitab kuning), communicative (active Arabic communication), and cultural (understanding Arab-Islamic cultural diversity). Practical implications include the need for policy support, interfaith dialogue between traditionalists and modernists, empirical research on innovation effectiveness, and documentation of best practices for wider adoption